2012
DOI: 10.1093/nar/gks687
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 inactivates PRH/Hhex using multiple mechanisms to de-repress VEGF-signalling genes and promote cell survival

Abstract: Protein kinase CK2 promotes cell survival and the activity of this kinase is elevated in several cancers including chronic myeloid leukaemia. We have shown previously that phosphorylation of the Proline-Rich Homeodomain protein (PRH/Hhex) by CK2 inhibits the DNA-binding activity of this transcription factor. Furthermore, PRH represses the transcription of multiple genes encoding components of the VEGF-signalling pathway and thereby influences cell survival. Here we show that the inhibitory effects of PRH on ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 24 publications
(65 reference statements)
0
53
0
Order By: Relevance
“…Interestingly, it was shown that phosphorylation of the Proline-Rich-Homeo domain protein PRH by CK2 inhibits the DNA binding activity of PRH. This inhibiting effect of PRH on genes encoding components of the VEGF signalling pathway is abrogated by CK2 phosphorylation [43] indicating that VEGF may be one target of CK2 in regulating angiogenesis. It was also recently shown that oxidized phospholipids induced the expression of VEGF in foetal human retinal pigment epithelial (RPE) cells [44].…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…Interestingly, it was shown that phosphorylation of the Proline-Rich-Homeo domain protein PRH by CK2 inhibits the DNA binding activity of PRH. This inhibiting effect of PRH on genes encoding components of the VEGF signalling pathway is abrogated by CK2 phosphorylation [43] indicating that VEGF may be one target of CK2 in regulating angiogenesis. It was also recently shown that oxidized phospholipids induced the expression of VEGF in foetal human retinal pigment epithelial (RPE) cells [44].…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…In Hhex -/-mice, HHEX/PRH was found to bind to the promoter regions of key members of the VEGF signaling pathway, such as VEGF, VEGF receptor (VEGFR)1, VEGFR2, and neuropillin-1, inhibiting their transcription, preventing cell proliferation, and playing a negative regulatory role in angiogenesis (Noy et al, 2010). The negative regulatory effect of HHEX/PRH on angiogenesis can be blocked by casein kinase 2 (Noy et al, 2012). We previously reported that VEGF was highly expressed in DMSCs derived from psoriatic skin lesions (Hou et al, 2014) and that for the treatment of psoriasis, TNF-α inhibition resulted in localized inhibition of Data are reported as means ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…CK2 has also been shown to inhibit the binding of PRH to DNA in cells. Ectopic over-expression of PRH in K562 cells represses transcription of the PRH target gene VEGFR-1 but this repression is lost on co-transfection with CK2α and β transgenes [48]. However, the repression of VEGFR-1 transcription by a PRH mutant in which phosphorylation of serine 163 and serine 177 is prevented by the replacement of these residues by cysteine residues is not inhibited by CK2 over-expression [48].…”
Section: Phosphorylation Of Prh Blocks Dna Bindingmentioning
confidence: 99%
“…Ectopic over-expression of PRH in K562 cells represses transcription of the PRH target gene VEGFR-1 but this repression is lost on co-transfection with CK2α and β transgenes [48]. However, the repression of VEGFR-1 transcription by a PRH mutant in which phosphorylation of serine 163 and serine 177 is prevented by the replacement of these residues by cysteine residues is not inhibited by CK2 over-expression [48]. Quantitative chromatin immunoprecipitation (ChIP) showed that CK2 over-expression does not prevent the binding of PRH S163C,S177C to the VEGFR-1 promoter as it does with wildtype PRH [48].…”
Section: Phosphorylation Of Prh Blocks Dna Bindingmentioning
confidence: 99%
See 1 more Smart Citation